PERTANGGUNGJAWABAN PIDANA TJIN LAM ALS ALAM DALAM TINDAK PIDANA KEPABEANAN (STUDI KASUS NOMOR 810/PID.B/2008/PN.PBR PERBANDINGAN PUTUSAN PENGADILAN NEGERI, PENGADILAN TINGGI DAN MAHKAMAH AGUNG) - JAHRI, ILFAN AFRIANDI; Diana, Ledy; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In the study of criminal responsibility Tjin Lam als Alam of a criminal offense of customs ( case study number 810 / Pid.B / 2008 / PN.PBR comparisons District Court , High Court and Supreme Court ) Pekanbaru District Court the accused was found guilty and sentenced to imprisonment for 1 ( one ) year and a fine of Rp . 50.000.000 , - ( Fifty million ) subsidiary 3 ( Three ) Months confinement. In Pekanbaru District Court, the defendant appealed to the High Court of Riau are getting the defendant was found not guilty and the Prosecution did Cassation to the Supreme Court the decision of the defendant not guilty . The purpose of this study , First : To determine whether Tjin lam natural als be held accountable in the case of customs. Second : To know how the judge's ruling on the level of the District Court , High Court and the Supreme Court had been right.This research is classified into normative research , namely that nature Descriptive - Analytical Methods , means to describe, record , analyze and interpret existing conditions. In this case the responsibility of customs criminal offenses between the ruling criminal offense of customs at the level of district courts , high courts and the Supreme Court and Judge assemblies good basis for consideration in the first instance , appellate up in the Supreme Court then examined carefully and drawn a conclusion.Conclusion first in liability cases customs Tjin lam als nature based on the decision of the District Court Pekanbaru found guilty of witness testimony I to witness VIII and completeness of the evidence such as ships and cargo that may lead to belong to the defendant, while the results of the decision of the High Court and the Supreme Court against with Pekanbaru District Court that the defendant was found not guilty by listening to witness testimony I to VIII witnesses which explains the absence of the accused where the time of arrest or at the location of the crime scene (TKP) at that time.Suggestions With the freedom of the judge in deciding a case, especially in criminal customs then should the judge must always strive to improve ourselves, increase experience and sharpen the analysis to determine the factors that are considered rational to base consideration of the decision, in order to reach a decision that has flavor justice and a need for community participation in preventing the crime of customs. Community participation can be done by an individual, group, corporation or business entity, and the institutions or organizations established by the community. Community participation can be implemented by obeying the laws and regulations on customs, to supervise the implementation of laws and regulations that apply particularly legislation on customs.Keywords : Accountability - Crime - Customs